Reducing the Burden of Heart Failure in Japan With Dapagliflozin ― A Cost Offset Model (IMPLICATION HF) - Kishi, Takuya; Kunikane, Eriko; Takagi, Hiroyuki; Chen, Jieling; Varela, Luis; Ozaki, Asuka (Circulation Reports, 2025)
Background: Dapagliflozin is clinically beneficial in heart failure (HF). However, how these clinical benefits translate into economic burden reduction is unclear. With IMPLICATION HF, we projected the reductions in HF events and costs that would result from dapagliflozin use in Japan using a cost offset model.Methods and Results: The modeled population comprised symptomatic HF patients from the DAPA-HF and DELIVER trials. We compared the event incidences and associated costs between HF treatment with and without dapagliflozin, using the prevalence, event rates, and event costs of HF in Japan from published literature, as well as the treatment effects of dapagliflozin from the pooled meta-analysis of DAPA-HF and DELIVER. The cumulative number of events (HF hospitalization [hHF], cardiovascular [CV] death, and all-cause death) and associated costs (hHF, CV death, total) were projected. Cost offsets were calculated according to the difference in event-related costs between HF treatment with and without dapagliflozin. Dapagliflozin was estimated to prevent 63,770 hHF events (number needed to treat [NNT] 20), 11,613 CV deaths (NNT 108), and 16,141 all-cause deaths (NNT 78), as well as reducing hHF and CV death costs by JPY62.7 billion and JPY16.6 billion, totaling JPY79.3 billion over 1 year in Japan. The sensitivity analyses corroborated these findings.Conclusions: The addition of dapagliflozin to HF treatment is projected to provide economic benefits to the Japanese healthcare system.